Rural Population of the Yenisei Province at the Turn of the XIX— XX Centuries: Socio-Demographic Dynamics - V. I. Fedorova (Научный диалог)
The dynamics of quantitative and qualitative changes in the rural population of the Yenisei region is revealed from the standpoint of the theory of demographic modernization. The stages and features of demographic processes in the subregion, due to its geo-economic position, the influence of the colonization factor on fertility, mortality, nuptiality, population growth rates, changes in the demographic behavior of the peasantry, and its ethnic composition are revealed. Based on the analysis of the current administrative statistics published by the provincial statistical committee in the annual “Reviews” of the province and “Commemorative books”, as well as the materials of the First All-Russian Population Census of 1897, the author comes to the conclusion that agrarian migrations in the region at the beginning of the 20th century acquired an explosive character, in contrast to a similar process in Western Siberia, which was extended over time. This led to the fact that the formation of a new demographic model, characteristic of modern society, took place in a specific way, since the features of the traditional model dominated in the resettlement environment: high birth rates and mortality, a large population of the peasant family, a younger age composition, intensive marriage, rare family divisions.